Evaluation of the Provision of Construction Support Through Business Entities (Case Study: Terbanggi Besar Kayu Agung Toll Road) - Hera Cahyaning Putri; Iris Mahani; Budi Hasiholan (Jurnal Indonesia Sosial Teknologi, 2024)
Generally, construction support is provided directly by the government, but in this case, the government provides construction support through other toll road business entities. The provision of construction support through toll road business entities on the Terbanggi Besar – Pematang Panggang – Kayu Agung Toll Road has financially increased the investment feasibility parameters, including an increase in the IRR value to 12% from the original 9.36% before the provision of construction support; The NPV value with the provision of construction support has a better NPV value, which is Rp. 3,875 T compared to the NPV value without construction support of - Rp. 2,044 T; The value of the payback period without the provision of construction support is 22 years and 3 months and with the provision of construction support for 19 years and 5 months. However, in the implementation process, the quality of toll road infrastructure at construction support locations is not met, resulting in business entities still having to participate in bearing quality risks to construction work carried out by the government. Business entities receiving construction support must bear maintenance costs due to repairs to damage to the construction support site. However, the increase in maintenance costs, in general, did not have a significant effect on the investment feasibility parameters of the Terbanggi Besar – Pematang Panggang – Kayu Agung toll road project. The increase in maintenance costs affected the decrease in IRR by 1.4%. The NPV indicator also decreased by Rp. 198 billion or 5.1%. The payback period has also increased from 19 years and 5 months to 19 years and 8 months. However, the mechanism for providing construction support through business entities needs to be considered to ensure that the benefits of providing construction support can be felt to the maximum.